Influence of Eastern Philosophy on Leo Tolstoy’s Idea of Perfection: An Analysis of the Concepts in “The Death of Ivan Ilyich” - Medelyan , Svetlana (Literatūra, 2025)
This research paper explores the influence of Eastern philosophy on Leo Tolstoy’s idea of perfection in his late period of work. The study is based on the assumption that the beginnings of this idea of Tolstoy are notions of the truth of life that can be perceived in the context of different cultural traditions. The main concepts of Eastern philosophy, with their emphasis on the inner perfection of man, had a significant influence on the Russian writer’s idea. Tolstoy studied Buddhism, Confucianism, and Taoism. Different, and sometimes even seemingly opposite points of view on certain aspects of human life in Tolstoy’s mind formed into a homogeneous concept of the way of a self-improving individual to personal and universal good or happiness. This concept is expressed in a certain way in the structure of the writer’s works of fiction.